Energy market, quality of life, and Sustainable Development: The EU consumers’ perspective - Veghes, Călin; Strâmbu-Dima, Andreea; Stoenică, Laurentiu (European Journal of Sustainable Development, 2025)
Energy has become one of the core aspects of the daily life of EU consumers, given the current marketing macroenvironment. The accelerated transition to green energy production and consumption has immediately impacted the quality of their daily lives with direct consequences in terms of the costs and comfort of their living. Increased energy expenditures and decreased home temperatures led to a mix of reactions in the form of migrating between suppliers, switching to green energy sources, or simply saving money by switching off lights and turning off heating. Three years have been enough to observe the emergence of an energy-matter expressed by an imbalance between the macro and microeconomic perspectives regarding the subject, with economic, social, and environmental consequences for all the stakeholders. The paper presents the results of an investigation conducted using secondary data and from a market-oriented perspective on consumers’ behavior regarding energy consumption, aiming to identify a path towards an organic transition balancing traditional and green energy sources to ensure the quality of life and support the sustainable development of the EU countries. Keywords: energy market, green transition, EU consumers, quality of life, sustainable development